Key challenges for the European welfare states - Rafael Mu\~noz de Bustillo Llorente (European Commission, Joint Research Centre (JRC), 2019)
Is the Welfare State sustainable? How has it fared in the last few decades? What are the main challenges facing the Welfare State today and in the near future? This Working paper aims at offering the reader with elements to answer, if temporarily, this questions regarding the present and future of the European Welfare State. With that aim, the paper discusses the evolution on European Welfare States, making emphasis in the contrast between the discourse that has become a common place regarding Welfare State dynamics and its crisis, and the picture shown by the indicators commonly used to measure the size of the Welfare State. Against this background, we review the 'old' and 'new' challenges faced by Welfare States. This review includes its compatibility with allocative efficiency and economic growth, the impact of globalisation and immigration, the increase in demographic dependency rates related to the growth of life expectancy and the reduction of fertility rates, the change in household patterns, or the growing concern about gender inequality. The last part of the paper deals with the different social and economic policy options available to the Welfare State to meet its goals in a context of economic and social change driven by the digital revolution.
Keywords: 330; Welfare State; Technical Change; Sustainability; Incentives; Globalization